Watch out: Themes in timepiece communities of counterfeit consumption. Issue 4 (25th June 2013) - Key, Thomas M.; Boostrom, Robert E.; Adjei, Mavis T.; Campbell, David A.
ABSTRACT: Although online communities of counterfeit consumption (OCCC) enhance the demand for counterfeit products, research that improves marketers' understanding of this phenomenon is lacking. This article's purpose is to investigate how online communities of consumption have transformed the acquisition, sharing, and processing of information by consumers of counterfeits. Through the use of netnography in an online counterfeit watch community, this work identifies four themes as factors that draw consumers to OCCC. The themes are technical competence of community members, willingness to pay, members' expectations of product performance, and trust in dealer. These communities strengthen consumer consumption of counterfeit products by broadening the ways in which consumers can engage, learn, identify, and ultimately decide to purchase counterfeit products. Managerial and theoretical implications are discussed. Copyright © 2013 John Wiley & Sons, Ltd.